Hypoglycemic activity of CPU2206: A novel peptide from sika (Cervus nippon Temminck) antler. Issue 12 (1st October 2019) - Wang, Wanqiu; Zhang, Junying; Yang, Xiaoting; Huang, Fengjie
Abstract: Previous work had extracted and purified an antidiabetic peptide named CPU2206 with 7, 127.6 Da. In this work, the toxicity of CPU2206 was first evaluated by daily administration to ICR mice, and after 28 days of administration, the body weight and lipid metabolism of the mice did not change significantly, which proved its safety and reliability. Second, further studies have focused on its hypoglycemic effects by daily intraperitoneal injection to alloxan‐induced diabetic mice and KK‐Ay mice, showing that CPU2206 effectively decreased the blood glucose and corresponding indicators of diabetic mice. Daily administration of CPU2206 nearly normalized the lipid metabolic parameters in diabetic mice. Histological examination also validated that CPU2206 ameliorated the pancreas injuries induced by alloxan or alleviated islet hypertrophy caused by insulin resistance in KK‐Ay mice. To sum up, a totally new bioactive peptide CPU2206 obtained from sika antler showed significantly antidiabetic as well as lipid‐lowering effects in diabetic mice. Practical applications: Antler has been used as a traditional Chinese medicine to invigorate primordial energy, enrich the blood, strengthen bones, and improve both male and female sexual functions for thousands of years. Traditionally, velvet antler can be grinded directly and taken orally, or used in porridge, wine and meat stew. Our experiment enriches the research on the function of edible antlers, provides the basis for developing it into functional health food, and on the other hand, provides an idea for finding new antidiabetic drugs.